ANALISIS YURIDIS FILOSOFIS TERHADAP PENETAPAN KEBIJAKAN TAX AMNESTY DI INDONESIA TERKAIT KONTEKS KEADILAN HUKUM - Lukiawan, Lukiawan; Demson Tiopan; Agus Setiawan; Yenny Yuniawaty (Berajah Journal, 2025)
The low tax ratio and the massive underground economy prompted the Government of Indonesia to implement the Tax Amnesty policy (Law Number 11 of 2016) as a pragmatic solution to accelerate state revenue. However, this study finds that the policy triggers a serious antinomy of norms within the Indonesian legal system. There is a diametrical conflict between the Tax Amnesty Law and the anti-money laundering regime (AML Law) as well as corruption eradication efforts (Anti-Corruption Law). The absolute confidentiality clause in Article 20 of the Tax Amnesty Law potentially hinders the principles of follow the money and asset tracing, thereby creating a risk of legalized money laundering for assets derived from crimes. Philosophically, this policy also violates Distributive Justice (Justitia Distributiva) and the principle of Equality Before the Law, as the state grants privileges in the form of penalty waivers to lawbreakers, while compliant taxpayers continue to bear the normal tax burden without equivalent incentives. This research employs a normative juridical method with statutory and conceptual approaches. The results conclude that although Tax Amnesty succeeded in increasing short-term liquidity, it fundamentally undermines legal certainty and the authority of the criminal justice system. Therefore, a Volume III Tax Amnesty is not recommended as it would exacerbate the erosion of voluntary compliance and validate moral hazard behavior.